Idiopathic subglottic stenosis: An evolving therapeutic algorithm. (8th August 2013) - Maldonado, Fabien; Loiselle, Andrea; DePew, Zachary S.; Edell, Eric S.; Ekbom, Dale C.; Malinchoc, Michael; Hagen, Clinton E.; Alon, Eran; Kasperbauer, Jan L.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Idiopathic subglottic stenosis (ISS) is a rare type of airway stenosis of unclear etiology. Open resection, while effective, remains a complex surgery and requires a hospital stay. Endoscopic management is often preferred but has historically been associated with a high recurrence rate. We aimed to analyze our experience, consisting of a standardized endoscopic approach combined with an empiric medical treatment. Study Design Retrospective cohort study. Methods All patients with ISS managed with standardized endoscopic treatment at our institution between 1987 and 2012 were identified, and their electronic medical records were reviewed. The treatment consisted of CO2 laser resection without dilatation and local infiltration with steroids and application of mitomycin C. Patients were also treated with antireflux medications, inhaled corticosteroids, and occasionally trimethoprim‐sulfamethoxazole. The influence of medical management on annual recurrence rate was analyzed using negative binomial logistic regression. Results A total of 110 patients treated with standardized endoscopic management were included in our analysis. The procedure was well tolerated by all patients without complications. Recurrences were observed in approximately 60% of patients at 5 years. There was a trend suggesting an association between aggressive medical treatment and a reduction in the rate of recurrence/person/year (relative risk = 0.52, P = 0.051). Conclusion A standardized endoscopic management of ISS consisting of CO2 laser vaporization of the fibrotic scar appears effective in symptom control, with 40% of patients not requiring retreatment in the follow‐up period, and with recurrence noted in a majority of patients. Aggressive medical treatment may have a role, but further prospective studies are required to confirm these findings. Level of Evidence 4. Laryngoscope, 124:498–503, 2014